Circular RNA circ_001350 regulates glioma cell proliferation, apoptosis, and metastatic properties by acting as a miRNA sponge. Issue 9 (24th April 2019) - Liu, Yang; Ma, Chunjie; Qin, Xiangying; Yu, Haiming; Shen, Lei; Jin, Haifeng
Abstract: Glioma is an aggressive malignancy with increasing incidence and threatens people's health worldwide. Accumulating evidence revealed that circular RNAs (circRNAs) play important functions in cancers. A previous study demonstrated that circ_001350 was elevated in glioma tissue samples than nontumorous tissue specimens screened by high‐throughput microarray. The level of circ_001350 in glioma tissue specimens and cell lines was detected by quantitative real‐time polymerase chain reaction. The Fisher exact test was carried out to estimate the correlation of circ_001350 level with clinical characteristics. Cell proliferation, apoptosis, and motility abilities were detected using cell counting kit‐8, clonogenic, flow cytometry, and transwell experiments, respectively. The potential target of circ_001350 was identified by the luciferase assay. circ_001350 level was significantly enhanced in glioma tissue specimens and cells. Further, elevated expression of circ_001350 was closely linked to patients' clinical severity. Knockdown of circ_001350 could inhibit cell proliferation and metastatic properties and increase apoptotic cells. circ_001350 could directly bind to miR‐1236 and regulate its expression to exert oncogenic functions. Collectively, circ_001350 directly sponges miR‐1236, thus contributing to malignant progression of glioma. Abstract : Upregulated circ_001350 is linked to glioma patients' adverse phenotypes. circ_001350 could directly sponge miR‐1236. The oncogenic functions of circ_001350 are partly dependent on its suppression of miR‐1236.